2010
DOI: 10.5614/itbj.sci.2010.42.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Historical Fire Detection of Tropical Forest from NDVI Time-series Data: Case Study on Jambi, Indonesia

Abstract: Abstract. In addition to forest encroachment, forest fire is a serious problem in Indonesia. Attempts at managing its widespread and frequent occurrence has led to intensive use of remote sensing data. Coarse resolution images have been employed to derive hot spots as an indicator of forest fire. However, most efforts to verify the hot spot data and to verify fire accidents have been restricted to the use of medium or high resolution data. At present, it is difficult to verify solely upon those data due to sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The principle of most geostationary satellite fire detection algorithms is essentially the same as that of Earth orbit satellite sensors [35][36][37][38], most of which depend on the threshold setting. In current fire products, the absolute brightness temperature or reflectivity value is typically used as the main recognition condition [39][40][41][42][43][44][45]. The important theoretical component behind the algorithm investigated here is to compare the difference between the radiation value and the background radiation of the point to be measured at two different times, combining space and time for overall analysis, and considering that the comparison between the central pixel and the surrounding pixels is affected by outliers.…”
Section: Calculation Of Time Series 1) Concept Of Algorithm Designmentioning
confidence: 99%
“…The principle of most geostationary satellite fire detection algorithms is essentially the same as that of Earth orbit satellite sensors [35][36][37][38], most of which depend on the threshold setting. In current fire products, the absolute brightness temperature or reflectivity value is typically used as the main recognition condition [39][40][41][42][43][44][45]. The important theoretical component behind the algorithm investigated here is to compare the difference between the radiation value and the background radiation of the point to be measured at two different times, combining space and time for overall analysis, and considering that the comparison between the central pixel and the surrounding pixels is affected by outliers.…”
Section: Calculation Of Time Series 1) Concept Of Algorithm Designmentioning
confidence: 99%
“…Goetz et al (2006), for instance, presented useful graphical representations of NDVI time-series data to assess post-fire forest regrowth in Canada. Present advance using X12-ARIMA demonstrated that time-series data were indispensable to characterize fire spot in tropical region (Panuju et al, 2010).…”
Section: Time-series Analysismentioning
confidence: 99%
“…Compared with geostationary satellites, polar-orbiting satellites can provide good resolution. At present, researchers have also carried out studies on the temporal information of polar-orbiting satellites [30][31][32], but how to integrate the spatial information still needs further exploration.…”
Section: Introductionmentioning
confidence: 99%